Analisis kemampuan koneksi matematis peserta didik dalam menyelesaikan soal pythagoras ditinjau dari gaya kognitif - Wardhana, Ibnu Rizki; Fuady, Anies (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study seeks to investigate the mathematical connectivity of students with field-dependent (FD) and field-independent (FI) cognitive styles in the context of solving Pythagorean puzzles. The research participants were two students from MTs Al Hidayah Karang Ploso, who had studied the Pythagorean theorem. Research data were acquired via interviews, cognitive style assessments, and the examination of mathematical connectivity skills. The veracity of the data was assessed through triangulation following the presentation and analysis of the summarized data. The instruments employed comprise the Group Embedded Figure Test for evaluating cognitive style and a mathematical connection ability assessment featuring three Pythagorean problems. The results indicated that the S-FI cognitive style effectively linked mathematical principles to real-world difficulties and situations. Conversely, S-FD cognitive type could only establish a restricted connection between mathematical concepts. The superior mathematical connection ability of the S-FI cognitive style compared to the S-FD cognitive style underscores the need of considering cognitive type in mathematics education.